2021
DOI: 10.1021/acsami.1c04583
|View full text |Cite
|
Sign up to set email alerts
|

Fe–Al–Si Thermoelectric (FAST) Materials and Modules: Diffusion Couple and Machine-Learning-Assisted Materials Development

Abstract: To lower the introduction and maintenance costs of autonomous power supplies for driving Internet-of-things (IoT) devices, we have developed low-cost Fe−Al−Si-based thermoelectric (FAST) materials and power generation modules. Our development approach combines computational science, experiments, mapping measurements, and machine learning (ML). FAST materials have a good balance of mechanical properties and excellent chemical stability, superior to that of conventional Bi− Te-based materials. However, it remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Silicon undergoes a eutectic transformation with aluminum [28], with a maximum melting temperature drop at 12.6 wt% of silicon. Silicon can also vary the degree of porosity [26]and the surface tension [29]. This also leads to a change in the morphology of the structure.…”
Section: Resultsmentioning
confidence: 99%
“…Silicon undergoes a eutectic transformation with aluminum [28], with a maximum melting temperature drop at 12.6 wt% of silicon. Silicon can also vary the degree of porosity [26]and the surface tension [29]. This also leads to a change in the morphology of the structure.…”
Section: Resultsmentioning
confidence: 99%
“…Iron monosilicide (FeSi) serves as a specific example of a strongly correlated electron system with d-electrons, garnering significant attention due to its unconventional temperature dependencies concerning magnetic, optical, elastic, transport properties, as well as its noncentrosymmetric crystal structure. FeSi is a narrow band gap semiconductor (0.18 eV) and a promising material for thermoelectric and solar applications. Notably, the thermoelectric material based on Fe 3 Al 2 Si 3 showcases substantial conductivity and Seebeck coefficient values, with the FeSi microstructure playing a pivotal role in yielding a high-power factor . Additionally, doping FeSi with aluminum is noted to result in a heavy-Fermion metal with unique characteristics .…”
Section: Introductionmentioning
confidence: 99%
“…8−10 Notably, the thermoelectric material based on Fe 3 Al 2 Si 3 showcases substantial conductivity and Seebeck coefficient values, with the FeSi microstructure playing a pivotal role in yielding a high-power factor. 11 Additionally, doping FeSi with aluminum is noted to result in a heavy-Fermion metal with unique characteristics. 12 The tuning of magnetic properties within a narrow band gap semiconductor and exploring its non-Fermi liquid state due to impurities hold fundamental interest within spintronics, 13 nonvolatile memory devices, 14 and quantum many-body physics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…When considering practical use of thermoelectric power-generation devices, the thermoelectric materials should consist of readily available elements, that is, low-cost materials such as β-FeSi 2 [4], MnSi γ [5], Fe 2 VAl Heusler compounds [6], Mg-Ag-Sb/Mg-Bi-Sb-Te [7], Cu-S [8], and Zn-Sb [9]. Recently reported Earthabundant Fe-Al-Si (τ 1 -Fe 3 Al 2 Si 3 ) ternary thermoelectric materials [10,11], which are called FAST materials [12,13], are promising candidates for fabricating robust power-generation modules using low-temperature waste heat at temperatures less than 500 K [13] because they have excellent oxidation resistance and mechanical properties [14]. Takagiwa et al have demonstrated operation of temperature/humidity sensors and wireless transmission by Bluetooth low-energy communication with power-generation modules using p-and n-type FAST materials [12].…”
Section: Introductionmentioning
confidence: 99%